IMPLEMENTATION OF TRANSLANGUAGING IN THE CONTEXT OF TEACHING MANDARIN IN INDONESIA IN HIGHER EDUCATION - Silalahi, Ronald Maraden Parlindungan; Guan, Nan (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2023)
As one of the many pedagogical strategies found in multilingual contexts, translanguaging can be a solution for learning foreign languages, especially Mandarin. It facilitates using multiple languages (outside the L2) for receptive and productive purposes. Its use can solve communication problems caused by students' language competence during teaching and learning. This study aims to determine the perceptions of Mandarin students at the higher education level in Indonesia regarding the application of translanguaging in class. The study was sequential explanatory design research using mixed research methods. Data collection was carried out in two stages: collecting quantitative data using a questionnaire and then collecting qualitative data through Group Interviews (GI). The distribution of the questionnaire was targeted at 100 students. GI was carried out on five students who had previously participated in filling out the questionnaire. This study shows that learning Mandarin at the tertiary level focuses on the monolingual-traditional learning model, oriented only to L2. Translanguaging is ideologically considered as a form of language incompetence. The higher the language skill, the less likely it is to find translanguaging. This study is expected to have implications for the development of learning Mandarin in a multilingual pedagogical context in Indonesia.